2021
DOI: 10.18632/aging.203611
|View full text |Cite
|
Sign up to set email alerts
|

Network pharmacology for systematic understanding of Schisandrin B reduces the epithelial cells injury of colitis through regulating pyroptosis by AMPK/Nrf2/NLRP3 inflammasome

Abstract: Ulcerative colitis (UC) is a chronic inflammatory disease with increasing incidence and prevalence in many countries. The purpose of this study is to explore the function of Schisandrin B and its underlying molecular mechanisms in colitis. In this study, mice with colitis were induced by giving 2.0% dextran sulfate sodium (DSS, MP) in the drinking water for seven days. Furthermore, TCMSP server and GEO DataSets were used to analyze the mechanism of Schisandrin B in colitis. It was found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 55 publications
0
21
0
Order By: Relevance
“…Schisandrin B treatment attenuated the vascular injury and fibrosis mediated by the endothelial to mesenchymal transition in vitro and in vivo [ 176 ]. Moreover, schisandrin B reduced epithelial cell injury in a model of colitis by modulating pyroptosis through AMPK/Nrf2/NLRP3 inflammasome pathways [ 177 ] as well as regulated STAT3-dependent Th17 cell differentiation and IL-17A cytokine release [ 178 ].…”
Section: Lignans With Antioxidant and Anti-inflammatory Actionmentioning
confidence: 99%
“…Schisandrin B treatment attenuated the vascular injury and fibrosis mediated by the endothelial to mesenchymal transition in vitro and in vivo [ 176 ]. Moreover, schisandrin B reduced epithelial cell injury in a model of colitis by modulating pyroptosis through AMPK/Nrf2/NLRP3 inflammasome pathways [ 177 ] as well as regulated STAT3-dependent Th17 cell differentiation and IL-17A cytokine release [ 178 ].…”
Section: Lignans With Antioxidant and Anti-inflammatory Actionmentioning
confidence: 99%
“…For the ROS involved in the activation of the NLRP3 inflammasome, the mitochondrial source is currently more recognized, namely, mitochondrial ROS (mtROS) [33,34]. Studies have confirmed that there is a close correlation between mitochondrial dysfunction and the activation of NLRP3 inflammasome [17]. Under the stimulation of various NLRP3 agonists, mitochondria become dysfunctional, and the production of mtROS increases, which leads to the formation of NLRP3 inflammasomes and the release of inflammatory mediators [35].…”
Section: Discussionmentioning
confidence: 99%
“…Schisandra chinensis, as a Chinese functional food, is rich in unsaturated fatty acids, minerals, vitamins, and proteins, and used as a tonic and sedative agent in traditional Chinese medicine [14][15][16]. Schisandrin A is one of the lignans isolated from the dried fruits of Schisandra chinensis [17,18]. It has a wide range of pharmacological effects in antioxidation, inhibition of apoptosis, and regulation of immunity [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…According to the active components identified based on TCMSP, we performed target fishing using the TCMSP and BATMEN-TCM, obtained a total of 264 potential targets of active components from SQSBD (Zhang et al, 2021). We also used GEO database to obtaine 1,505 differential expression genes (DEGs) of AML.…”
Section: Discussionmentioning
confidence: 99%